Plasma PCSK9 correlates with apoB-48-containing triglyceride-rich lipoprotein production in men with insulin resistance - Drouin-Chartier, Jean-Philippe (J Lipid Res, 2018)
Intestinal triglyceride (TG)-rich lipoproteins (TRLs) are important in the pathogenesis of atherosclerosis in insulin resistance (IR). We investigated the association of plasma proprotein convertase subtilisin/kexin type 9 (PCSK9) concentrations with apoB-48-containing TRL metabolism in 148 men displaying various degrees of IR by measuring in vivo kinetics of TRL apoB-48 during a constant-fed state after a primed-constant infusion of L-[5,5,5-D3]leucine. Plasma PCSK9 concentrations positively correlated with TRL apoB-48 pool size (r = 0.31, P = 0.0002) and production rate (r = 0.24, P = 0.008) but not the fractional catabolic rate (r = −0.04, P = 0.6). Backward stepwise multiple linear regression analysis identified PCSK9 concentrations as a positive predictor of TRL apoB-48 production rate (standard β = +0.20, P = 0.007) independent of BMI, age, T2D/metformin use, dietary fat intake during the kinetic study, and fasting concentrations of TGs, insulin, glucose, LDL cholesterol, or C-reactive protein. We also assessed intestinal expression of key genes involved in chylomicron processing from duodenal samples of 71 men. Expression of PCSK9 and HMG-CoAR genes was positively associated (r = 0.43, P = 0.002). These results support PCSK9 association with intestinal secretion and plasma overaccumulation of TRL apoB-48 in men with IR.